Pengaruh Satisfaction, Brand Love terhadap Brand Loyalty dan Word of Mouth - Edy Purwanto; M. Munir Syam AR (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study aims to examine and determine the effect of consumer satisfaction, brand love on loyalty and WOM, and the influence of customer loyalty on WOM. The object of this research is Batik in Sumenep Regency. The sample for this study consisted of 200 people who were selected using the purposive sampling technique. The questionnaire was distributed to collect data. Path analysis and structural equation modeling were used in the test. Results-Based on this research, the variable of satisfaction has an influence on loyalty and word of mouth, love of the brand has an effect on loyalty, and customer loyalty has an effect on WOM. But the variable love of the brand has no significant effect on word of mouth. It is hoped that the research can provide information about the ability of satisfaction and brand love in influencing consumer loyalty and the ability of satisfaction and loyalty in influencing consumers to carry out the word of mouth. Furthermore, this research is useful for clothing business actors in the batik industry in developing appropriate strategies in developing their businesses.